Studi Kelayakan Penginputan Keilmuan Image Processing pada Kurikulum Prodi Pendidikan Teknik Elektro Universitas Negeri Padang - Arinda Frismelly; Riki Mukhaiyar (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2020)
The existence of technological development requires a curriculum to adjust to technological developments that occur. The need for curriculum development in order to meet human needs and improve student competence in facing existing technological developments. To produce competent students in the field of Electrical Engineering Education, a good curriculum is needed. To get a good curriculum evaluation or enrichment must always be done. Curriculum enrichment can be done one of them by inputting a course that is image processing. Image processing subject is one of the engineering courses at Non-LPTK University. Where the composition of courses at the University of LPTK includes general courses, engineering courses, and professional expertise courses. Thus, image processing courses can be assimilated into the UNP Electrical Engineering Education curriculum. The results show that image processing courses can be assimilated into the PSPTE FT UNP curriculum with learning outcomes that are in accordance with the characteristics of the PSPTE FT UNP curriculum that students are expected to be able to understand and explain the basic concepts of the image processing course.